External Audit And The Reliability Of Financial Statements In A Context Of Digital Transformation - Behilil ,Zeneb (University of Eloued جامعة الوادي, 2025)
This study investigates the impact of digital transformation on financial statement reliability in the Algerian auditing context. Based on a quantitative approach, 100 professionals, including external auditors, internal auditors, financial managers and accountants were surveyed and computed using SPSS and Excel. Due to non-normal data distribution, Spearman rho and Chi-square tests were performed, followed by an Ordinal Logistic Regression (OLR) model to find the impact of predictors on perceived reliability. Results show that auditors' IT capability and compliance with audit standards have the biggest effects and use of tools and organizational obstacles have smaller effects. The OLR model provides a good fit, confirming the robustness of findings. Overall, digital transformation, based on competence and governance, improves audit quality.
مقال
Keywords: Digital transformation; Financial statement reliability; Digital accounting revolution; Audit technologies; Blockchain.